URBAN-RURAL DISPARITY: THE UTILIZATION OF PRIMARY HEALTHCARE CENTERS AMONG ELDERLY IN EAST JAVA, INDONESIA - Ratna Dwi Wulandari; Agung Dwi Laksono (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2019)
Background: Urban always attracts investors to invest. Health facilities in urban areas are growing rapidly compared to villages. This condition is estimated to contribute to the disparity of urban-rural areas in the utilization of health services. Studying the utilization of health services is a way to evaluate the performance of the health care system through its output.Aim: This study analyzed the urban-rural disparity in the utilization of primary healthcare center by the elderly.Method: This study used in the 2013 Basic Health Research raw data. The 2013 Basic Health Research was designed as a cross-sectional survey. With the multi-stage cluster random sampling method, 25,813 elderly people in East Java Province participated. Data were analyzed using Multinomial Logistic Regression tests.Results: Elderly people in urban areas have a better probability of outpatient use of 1.208 than those living in rural areas (OR 1.208; 95% CI 1.057-1.380). The elderly who have a primary school and under education have the possibility of 1.558 times more utilizing outpatients in primary healthcare centers than the elderly who have college education levels (OR 1.558; 95% CI 1.001-2.424).Conclusion: There was a disparity between urban and rural areas in the utilization of outpatient primary healthcare centers in East Java by the elderly. Policymakers in East Java are recommended to improve facilities and infrastructure of the primary healthcare centers in rural areas by paying attention to the results of this study.Keywords: elderly, urban-rural disparities, primary healthcare center, healthcare utilization, inpatient-outpatient.